AN OVERVIEW ON MEDICINAL PROPERTIES OF ALOE VERA: ANTIBACTERIAL & ANTIFUNGAL ASPECTS - AMEETA SHARMA; SHIKHA GAUTAM (International Journal of Pharma and Bio Sciences, 2013)
Aloe Vera is attracting the attention of scientists, researchers, and people around the world once again. Because of the multiple uses of Aloe Vera, and the easy growth and maintenance of the plant, many researchers of public and private sector have gained interest in this plant. Many novel and effective uses of Aloe Vera have come in light due to the researches on Aloe Vera in the field of biology, biochemistry and clinical studies. The beneficial effectiveness of Aloe in wound healing and being an anti-inflammatory is due to some constituents of Aloe that are involved in the healing process. According to the recent studies, the presence of mannose-6-phosphate, the important sugar in the Aloe gel, is mainly responsible for the wound healing properties of Aloe Vera, and thus considered its possibility of being an active growth substance. Scientist found an innovative and interesting usage of Aloe Vera gel as an edible coating on fruits and vegetables that act as the healthy preservative coating and thus will preserve the quality and safety of fruits during cold storage. This study was done on papaya that resulted in its subsequent increase in shelf life. The gel also offers protection from some of the dangerous pathogens by inhibiting their growth, and it also provides numerous health benefits. It is because of this reasons, Aloe products are so popular in the market and are widely used in skin care, cosmetics, medical, health care and food industry.